Kehujjahan Hadist Aha ̅d - Zuhri, Ahmad (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The ah d hadith is often contradicted with the mutaw tir hadith, so in terms of its definition it is also mentioned that the ah d hadith is a hadith whose number of narrators does not reach the number of mutaw tir hadith narrators. The mutaw tir hadith status is qat'iy al-wur d, while the ah d hadith is zanniy, because in the process of narration there may be errors or errors from the narrators, therefore, not all ah d hadiths can be accepted or can be used as a hujjah.